APLIKASI SISTEM INFORMASI GEOGRAFIS DALAM MEMPREDIKSI EROSI DENGAN METODE USLE DI SUB DAS DUMOGA - Surono Surono; Jailani Husain; Yani E.B. Kamagi; Jeane Lengkong (COCOS, 2013)
AbstractThe objective this study was to predict erosion rate and erosion hazard level in DumogaSub-watershed. The study is expected to provide spatial information on erosion rateand erosion hazard level in Dumoga Sub-watershed, particularly for spatial planning as wellas soil and water conservation. Erosion was predicted employing USLE while spatial analysiswas conducted using Geographic Information Systems (ArcView 3.3). Rainfall data were collectedfrom three weather stations, erodibility values obtained by analyzing samples fromthree soil types, slope categories were determined using DEM (Digital Elevation Model), valuesof the landuse and soil conservation were determined by means of satellite image interpretationin and field survey as well. It was found that soil erosion ranged from 0.39 to16.800 tonnes /ha/year. The lowest erosion rate occurred on forest land and ricefield withhacingflatslope. The highest erosion rate was identified on farm land having very steep slope.Erosion hazard level varied from verylow to very severe. It is necessary to perform soil andwater conservation measured on the land experiencing severe to very severe erosion hazardas to reduce soil erosion.Keywords: Erosion, Geographic Information System, Watersheed